Tác động của quản trị nguồn nhân lực xanh đến hành vi đổi mới sáng tạo xanh dưới sự ảnh hưởng của bản sắc xanh và chia sẻ kiến thức xanh: Nghiên cứu tại các doanh nghiệp trên địa bàn Thành phố Hồ Chí Minh - Tăng Mỹ , Sang; Nguyễn Quốc , Anh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
Innovation will be the new growth engine for Vietnamese businesses. The purpose of this article is to evaluate the impact of green human resource management on green innovation through the lenses of green organizational identity and green knowledge sharing. The survey sample included 338 people who worked in businesses in Ho Chi Minh City. The PLS-S was employed to process and analyze the collected data in two stages. The research results show that green human resource management has a direct impact on green organizational identity, green knowledge sharing, and green innovation. Green organizational identity and green knowledge sharing have direct impacts on green innovation. Furthermore, the findings show that organizational identity and green knowledge sharing act as a bridge between green human resource management and green innovation. This study investigates the impact of green human resource management on green innovation behavior in Vietnam, as influenced by green identity and green knowledge sharing.